W. Va. Code 897-98, ch. 148, §7 (2d. ed. 1887) - (:unkn) unknown (My University, 1887)
Prohibited the carry of any revolver or other pistol, dirk, Bowie-knife, razor, slung-shot, billy, metallic or other false knuckles, or any other dangerous or deadly weapon of like kind or character. Violators guilty of a misdemeanor, fined not less than twenty-five nor more than two hundred dollars.
Keywords: CARRY